Robotics Based Strategies to Support Computational Thinking: The Case of the Pascual Bravo Industrial Technical Institute - García, Maritza A. (2017)
At present there are different public and private companies that support the Colombian government in the initiative of taking the technological processes and of research and innovation to the classrooms in order to generate a knowledge that propitiates great changes in the society and that at the same time helps to mitigate some national problematic. This generates great changes inside the school and the student, achieving significant learning in various areas of knowledge such as environmental, physical, electronic, mathematics, programming, and mechanics, among others. This article presents some strategies, such as robotics clubs, and how their problem-based teaching methodology collaborates in the development of competences of various types and the achievement of computational thinking in students. In addition, mention is made of the results of the project developed at the Pascual Bravo Industrial Technical Institute in Medellin-Colombia, which was presented at the XXII CACIC Congress in Argentina.